Method for degrading acetaminophen in water body by activating persulfate with iron-doped carbon quantum dots

The iron-doped carbon quantum dot and persulfate photocatalytic system prepared by hydrothermal reaction solves the problems of low degradation efficiency and complex process in the prior art, and achieves an efficient and low-cost water removal effect.

CN119176606AInactive Publication Date: 2024-12-24HUNAN UNIV

Patent Information

Application Number
CN202411373647.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has low degradation efficiency of acetaminophen during photoactivation of persulfate and has problems such as complex process and easy to lead to the risk of secondary pollution.

Method used

Iron-doped carbon quantum dots are prepared through hydrothermal reaction using ferrous gluconate as raw material, and photocatalytic degradation is carried out in combination with persulfate to form a highly efficient hybrid oxidation system dominated by hydroxyl radicals.

Benefits of technology

The 100% degradation rate of acetaminophen is achieved, with simple process, low cost, extremely low catalyst and oxidant amount, excellent removal effect and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176606A_ABST
    Figure CN119176606A_ABST
Patent Text Reader

Abstract

The invention discloses a method for degrading acetaminophen in a water body by activating persulfate with iron-doped carbon quantum dots. According to the method, the acetaminophen-containing water body is degraded by activating the persulfate with the iron-doped carbon quantum dots. Wherein the iron-doped carbon quantum dots are prepared by taking ferrous gluconate as a raw material, carrying out hydrothermal reaction at 180-220 DEG C and dialyzing. According to the method disclosed by the invention, the persulfate can be effectively activated by using light energy in an activation process dominated by a photo-generated hole to generate more free radicals and non-free radical species, namely an efficient mixed oxidation system of a free radical pathway dominated by hydroxyl free radicals and a non-free radical pathway dominated by singlet oxygen is formed; the method has the advantages of being simple in process, convenient to operate, low in cost, extremely low in catalyst addition amount, low in oxidant addition amount, high in utilization rate, high in degradation efficiency, good in removal effect, environmentally friendly and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalytic advanced oxidation treatment of environmental pollutants, and specifically relates to a method for degrading acetaminophen in water by activating persulfate using iron-doped carbon quantum dots. Background Art

[0002] With the widespread use of industrial products and various foods and medicines, the threat of organic pollutants in water bodies is gradually receiving attention. Organic pollutants can destroy the ecological balance of water bodies, seriously pollute drinking water sources, and cause great harm to human bodies, soil, etc. Therefore, it is urgent to explore economical and effective water treatment technologies to remove organic pollutants in water bodies, thereby eliminating the hidden dangers of organic pollutants in water bodies.

[0003] The photocatalytic advanced oxidation process based on peroxymonosulfate is considered to be a promising method due to its high oxidation capacity, strong economy, strong environmental adaptability, and easy storage and transportation. - Directly oxidize pollutants and produce active substances (such as OH, 1 O2、SO4 - ·), effectively oxidizing organic pollutants in the environment. In the research and practice of photoactivated peroxymonosulfate, most researchers mainly achieve the activation of peroxymonosulfate and the removal of organic pollutants by inducing electron transfer pathways, but this method has the disadvantages of low degradation efficiency and poor removal effect.

[0004] Carbon quantum dots, due to their small size effect, good photoresponse and excellent carrier migration, show great potential as suitable PMS activators. At the same time, due to their simple synthesis method, cheap and readily available precursors, carbon quantum dots have become a promising carbon-based material for wastewater treatment. However, the poor internal electron transfer efficiency makes the catalytic efficiency of carbon quantum dots low, which limits the further application of carbon quantum dots. Based on this, the electronic structure of carbon quantum dots can be changed by doping with metal elements, thereby adjusting the energy gap or band gap on which the optical properties of carbon quantum dots depend. Taking iron-doped carbon quantum dots as an example, iron source, carbon source and ethylenediamine are usually used as raw materials. However, this synthesis method has problems such as complex process and easy to cause secondary pollution risks. Therefore, how to obtain a paracetamol removal system with low catalyst and low oxidant dosage is of great significance for achieving effective photoactivated persulfate and efficient degradation of paracetamol. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots, which has the advantages of simple process, convenient operation, low cost, extremely low catalyst dosage, low oxidant dosage and high utilization rate, fast degradation efficiency, good removal effect and environmental friendliness.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions.

[0007] A method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots, wherein the method comprises degrading the acetaminophen-containing water by activating persulfate with iron-doped carbon quantum dots; the iron-doped carbon quantum dots are prepared by using ferrous gluconate as a raw material through hydrothermal reaction and dialysis; and the temperature of the hydrothermal reaction is 180°C to 220°C.

[0008] The above method is further improved in that the hydrothermal reaction time is 5h to 8h.

[0009] The above method is further improved, and the preparation method of the iron-doped carbon quantum dots comprises the following steps: subjecting the ferrous gluconate solution to a hydrothermal reaction, filtering and dialyzing to obtain the iron-doped carbon quantum dots.

[0010] The above method is further improved, wherein the concentration of ferrous gluconate in the ferrous gluconate solution is 0.1 mol / L to 0.3 mol / L, and the preparation process of the ferrous gluconate solution is: mixing ferrous gluconate and water to obtain the ferrous gluconate solution; the mixing time is 10 min to 30 min, and the mixing is carried out under stirring conditions.

[0011] The above method is further improved in that the pore size of the filter membrane used in the filtration is 0.22 μm, the dialysis time is 24 h to 60 h, the molecular weight of the dialysis bag used in the dialysis is 500 Da, and the dialysis is performed under light-proof conditions.

[0012] The above method is further improved, wherein the degradation treatment is: mixing iron-doped carbon quantum dots with water containing acetaminophen, adding persulfate under light conditions to carry out a photocatalytic degradation reaction to achieve degradation of acetaminophen in the water.

[0013] The above method is further improved in that the ratio of the iron-doped carbon quantum dots to the water containing acetaminophen is 1 μg-100 μg:1L, and the ratio of the persulfate to the water containing acetaminophen is 50 μmol-500 μmol:1L.

[0014] The above method is further improved, wherein the initial concentration of acetaminophen in the acetaminophen-containing water body is 1 mg / L to 20 mg / L, the initial pH value of the acetaminophen-containing water body is 3 to 10, the persulfate is peroxymonosulfate, and the peroxymonosulfate is potassium hydrogen peroxymonosulfate.

[0015] The above method is further improved in that the mixing time is 30min to 60min, the mixing is carried out under light-proof and stirring conditions, the photocatalytic degradation reaction time is 10min to 20min, and the photocatalytic degradation reaction temperature is 10°C to 30°C.

[0016] The above method is further improved, wherein the illumination is visible light, the wavelength of the visible light is 420nm, the average light intensity of the visible light is 0.25W-0.35W, and the height of the light source used for the visible light from the water surface is 10cm-20cm.

[0017] Compared with the prior art, the advantages of the present invention are:

[0018] The present invention provides a method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots. The iron-doped carbon quantum dots are prepared by hydrothermal reaction at 180°C to 220°C and dialysis using ferrous gluconate as a raw material. The iron-doped carbon quantum dots used in the present invention have rich -OH and -COOH structures as a precursor, and the iron is in the form of Fe 2+ The method of the present invention is connected to the carbon skeleton in the form of, without adding other carbon sources and organic matter, only through hydrothermal reaction and dialysis, iron-doped carbon quantum dots with more hydroxyl groups and richer active sites can be obtained, and the synthesis method is green and simple. The method of the present invention, the activation process dominated by photogenerated holes can effectively utilize light energy to activate persulfate, produce more free radicals and non-free radical species, that is, form a free radical pathway dominated by hydroxyl radicals and a non-free radical pathway dominated by singlet oxygen. An efficient mixed oxidation system, thereby realizing the deep oxidation degradation of acetaminophen. The method of the present invention, the degradation rate of acetaminophen reaches 100% within 20min, can realize the thorough removal of acetaminophen in water, has the advantages of simple process, convenient operation, low cost, extremely low catalyst dosage, low oxidant dosage and high utilization rate, fast degradation efficiency, good removal effect, environmental friendliness, etc., and has practical significance for the treatment of acetaminophen wastewater in the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a TEM image of the iron-doped carbon quantum dots (Fe-CDs) prepared in Example 1 of the present invention.

[0020] Figure 2This is the XRD pattern of the iron-doped carbon quantum dots (Fe-CDs) prepared in Example 1 of the present invention.

[0021] Figure 3 This is a Raman spectrum of iron-doped carbon quantum dots (Fe-CDs) and carbon quantum dots (CDs) prepared in Example 1 of the present invention.

[0022] Figure 4 UV-Vis-DRS images of iron-doped carbon quantum dots (Fe-CDs) and carbon quantum dots (CDs) prepared in Example 1 of the present invention.

[0023] Figure 5 This is a diagram showing the degradation effects of different reaction systems on acetaminophen in Example 1 of the present invention.

[0024] Figure 6 This is a diagram showing the degradation effect of iron-doped carbon quantum dots on acetaminophen at different iron-doped carbon quantum dot addition amounts in Example 2 of the present invention.

[0025] Figure 7 This is a diagram showing the degradation effect of iron-doped carbon quantum dots on acetaminophen at different addition amounts of potassium permonosulfate in Example 3 of the present invention.

[0026] Figure 8 This is a diagram showing the degradation effect of iron-doped carbon quantum dots on acetaminophen under different pH conditions in Example 4 of the present invention.

[0027] Fig. 9 This is a diagram showing the degradation effect of iron-doped carbon quantum dots on acetaminophen under different quenching agent conditions in Example 6 of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.

[0029] Embodiment 1:

[0030] A method for degrading acetaminophen in water by using iron-doped carbon quantum dots to activate persulfate is disclosed, specifically using iron-doped carbon quantum dots to activate persulfate to degrade acetaminophen-containing water, comprising the following steps:

[0031] 1.2 μg of iron-doped carbon quantum dots (Fe-CDs) were weighed and added to 50 mL of 5 mg / L acetaminophen solution (the initial pH of the solution was 5.85). The temperature was maintained at 25°C using a low-temperature circulating water device and stirred in the dark for 30 minutes to reach adsorption-desorption equilibrium. Then, 50 mL of potassium permonosulfate solution (chemical formula: KHSO5) (PMS) was added to make the concentration of potassium permonosulfate in the system 0.2 mM. A photocatalytic degradation reaction was carried out under visible light for 20 minutes. The parameters of the visible light were: wavelength 420 nm, average light intensity 0.30 W, and the height of the visible light source from the water surface was 15 cm to complete the degradation of acetaminophen in the water.

[0032] Control group 1 (Fe-CDs+Vis): only Fe-CDs were added without PMS, and other conditions were the same.

[0033] Control group 2 (PMS+Fe-CDs / ): no visible light was used, and other conditions were the same.

[0034] Control group three (PMS+Vis): only PMS was added without Fe-CDs, and other conditions were the same.

[0035] Control group 4 (PMS): only PMS was added, no Fe-CDs were added, no visible light was used, and other conditions were the same.

[0036] Control group five (CDs+PMS+Vis): Carbon quantum dots (CDs) were used to replace Fe-CDs, and other conditions were the same.

[0037] Control group 6 (CDs+PMS): Carbon quantum dots (CDs) were used instead of Fe-CDs, visible light was not used, and other conditions were the same.

[0038] Control group seven (CDs+Vis): Carbon quantum dots (CDs) were used to replace Fe-CDs, PMS was not added, and other conditions were the same.

[0039] Control group VIII (Vis): No Fe-CDs and PMS were added, and other conditions were the same.

[0040] Control group 9 (Fe 3+ +PMS+Vis): using Fe 3+ solution to replace Fe-CDs, and other conditions were the same.

[0041] In this embodiment, the method for preparing iron-doped carbon quantum dots (Fe-CDs) comprises the following steps:

[0042] (1) Weigh 3.0 g of ferrous gluconate and add it to 60 mL of ultrapure water. Stir for 10 min to make it evenly suspended to obtain a ferrous gluconate solution.

[0043] (2) The ferrous gluconate solution was poured into a reactor, subjected to a hydrothermal reaction at 200° C. for 6 h, and impurities were filtered out with a 0.22 μm filter membrane. The solution was then dialyzed for 48 h using a dialysis bag with a molecular weight of 500 Da under light-proof conditions to obtain iron-doped carbon quantum dots, which were named Fe-CDs.

[0044] In this embodiment, the method for preparing carbon quantum dots (CDs) includes the following steps:

[0045] (1) Weigh 3.0 g of glucose and add it to 60 mL of ultrapure water. Stir for 10 min to mix well to obtain a glucose solution.

[0046] (2) The glucose solution was poured into a reactor and subjected to a hydrothermal reaction at 200° C. for 6 h. Impurities were filtered out with a 0.22 μm filter membrane, and then dialyzed for 48 h using a dialysis bag with a molecular weight of 1000 Da under light-proof conditions to obtain carbon quantum dots, which were named CDs.

[0047] During the catalytic degradation reaction, 1 mL of the reaction solution was taken at time points of 0 min (adsorption 30 min), 4 min, 8 min, 12 min, 16 min, and 20 min, filtered with a 0.22 μm filter head, and added to a liquid injection bottle containing 20 μL of 100 mM sodium thiosulfate solution, and the concentration of acetaminophen in the solution was detected by HPLC.

[0048] Figure 1 TEM image of the iron-doped carbon quantum dots (Fe-CDs) prepared in Example 1 of the present invention. Figure 1 It can be seen that the iron-doped carbon quantum dots exhibit a dot-like structure, and in the enlarged HRTEM image, the lattice fringes are measured to be 0.35nm and 0.21nm, which indicates that the iron oxide (Fe2O3) and amorphous carbon (100) crystal planes correspond well.

[0049] Figure 2 The XRD pattern of the iron-doped carbon quantum dots (Fe-CDs) prepared in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that the position of the diffraction peak of iron-doped carbon quantum dots (Fe-CDs) is around 21°, and the shape is a wide and short peak, which is consistent with the diffraction peak characteristics of amorphous carbon. This shows that the main phase composition of the iron-doped carbon quantum dots (Fe-CDs) of the present invention is amorphous carbon.

[0050] Figure 3The Raman spectra of the iron-doped carbon quantum dots (Fe-CDs) and carbon quantum dots (CDs) prepared in Example 1 of the present invention are shown in FIG. Figure 3 It can be seen that the intensity ratios of D band and G band of Fe-CDs and CDs are 2.414 and 2.326, respectively, indicating that Fe-CDs are highly graphitized and more defects are formed on the surface.

[0051] Figure 4 The UV-Vis-DRS images of the iron-doped carbon quantum dots (Fe-CDs) and carbon quantum dots (CDs) prepared in Example 1 of the present invention are shown in FIG. Figure 4 It can be seen that the absorption edge of Fe-CDs is red-shifted and has a stronger absorption range in the range of 320nm to 600nm, which indicates that the introduction of iron atoms helps to improve the visible light absorption ability of Fe-CDs.

[0052] Figure 5 The figure is a graph showing the degradation effects of different reaction systems on acetaminophen in Example 1 of the present invention. Figure 5 It can be seen that within 20 minutes of degradation reaction, the degradation rates of Vis group, PMS group, PMS+Vis group, Fe-CDs+Vis group and CDs+Vis group were 0.15%, 0.42%, 6.04%, 1.14% and 1.55%, respectively. The degradation rates of acetaminophen in the above five reaction systems were all very low; the degradation rate of PMS+Fe-CDs group was 40.86%; CDs+PMS+Vis group could only adsorb 0.21% of acetaminophen after reaching adsorption equilibrium, but the degradation rate of acetaminophen did not exceed 20% within 20 minutes of degradation reaction; Fe 3+ The degradation rate of the +PMS+Vis group was no more than 20%; the PMS+Fe-CDs+Vis group could adsorb 1.90% of acetaminophen after reaching adsorption equilibrium, and the degradation rate of acetaminophen was 100% within 20 minutes of degradation reaction. It can be seen that under visible light conditions, the iron-doped carbon quantum dots (Fe-CDs) of the present invention and PMS showed a significant synergistic effect. The Fe on the Fe-CDs 3+ The site is an important active site, which enables PMS to be efficiently catalyzed and utilized, thereby effectively degrading acetaminophen.

[0053] In summary, under the conditions of an initial pH of 5.85, a PMS concentration of 0.2 mM, and a Fe-CDs catalyst dosage of 12 μg / L, Fe-CDs exhibited excellent catalytic performance and was able to degrade 100% of acetaminophen within 20 min. The iron-doped carbon quantum dots (Fe-CDs) of the present invention can achieve efficient removal of acetaminophen.

[0054] Embodiment 2:

[0055] The effects of different amounts of iron-doped carbon quantum dots (Fe-CDs) added on the degradation of acetaminophen were investigated. Specifically, the acetaminophen-containing water was degraded by using iron-doped carbon quantum dots to activate persulfate, including the following steps:

[0056] 0.6 μg, 1.2 μg, 1.8 μg, and 2.4 μg of the iron-doped carbon quantum dots (Fe-CDs) in Example 1 were weighed respectively, added to 50 mL, 5 mg / L acetaminophen solution (the initial pH of the solution was 5.8), and the temperature was maintained at 25° C. using a low-temperature circulating water device. Stir for 30 min in the dark to reach adsorption-desorption equilibrium; then, 50 mL of potassium permonosulfate solution (PMS) was added so that the concentration of PMS in the system was 0.2 mM, and a photocatalytic degradation reaction was carried out under visible light for 20 min to complete the degradation of acetaminophen in the water.

[0057] Figure 6 The figure is a graph showing the degradation effect of iron-doped carbon quantum dots on acetaminophen at different iron-doped carbon quantum dot addition amounts in Example 2 of the present invention. Figure 6 It can be seen that when the addition amount of iron-doped carbon quantum dots (Fe-CDs) increases from 6 μg / L to 24 μg / L, the degradation efficiency of acetaminophen first increases and then remains unchanged. It can be seen that increasing the amount of catalyst has little effect on the removal effect of acetaminophen.

[0058] Embodiment 3:

[0059] The effects of different potassium permonosulfate additions on the degradation of acetaminophen were investigated. Specifically, the acetaminophen-containing water was degraded by using iron-doped carbon quantum activated persulfate, including the following steps:

[0060] Weigh 3 portions of 1.2 μg of the iron-doped carbon quantum dot catalyst (Fe-CDs) in Example 1, respectively add 50 mL of a 2.5 mg / L acetaminophen solution (the initial pH of the solution is 5.8), maintain the temperature at 25 ° C using a low-temperature circulating water device, stir in the dark for 30 min to reach adsorption-desorption equilibrium; then add potassium permonosulfate (PMS) so that the concentration of PMS in the system is 0.1 mM, 0.3 mM and 0.4 mM, respectively, and carry out photocatalytic degradation reaction under visible light for 20 min to complete the degradation of acetaminophen in the water.

[0061] Figure 7 The figure is a graph showing the degradation effect of iron-doped carbon quantum dots on acetaminophen at different potassium permonosulfate addition amounts in Example 3 of the present invention. Figure 7It can be seen that when the dosage of potassium monopersulfate increased from 0.1 mmol / L to 0.4 mmol / L, the degradation rate of acetaminophen gradually increased, which indicates that iron-doped carbon quantum dots can effectively activate potassium monopersulfate and achieve effective removal of pollutants.

[0062] Embodiment 4:

[0063] The effect of different pH conditions on the degradation of acetaminophen was investigated. Specifically, the acetaminophen-containing water was degraded by using iron-doped carbon quantum activated persulfate, including the following steps:

[0064] Take 5 parts of acetaminophen solutions (the concentration of the solution is 5 mg / L, the volume is 50 mL, and the initial pH is 5.84), use 0.1 mol / L hydrochloric acid and 0.1 mol / L sodium hydroxide solution to adjust the pH of 4 parts of the acetaminophen solutions to 3, 5, 7, and 9, respectively, add 1.2 μg of iron-doped carbon quantum dots (Fe-CDs) in Example 1, respectively, use a low-temperature circulating water device to maintain the temperature at 25°C, stir in a dark place for 30 min, and reach adsorption-desorption equilibrium; then, add potassium permonosulfate (PMS) so that the concentration of PMS in the system is 0.2 mM, carry out photocatalytic degradation reaction under visible light for 20 min, and complete the degradation of acetaminophen in the water.

[0065] During the photocatalytic degradation reaction, 1 mL of the reaction solution was taken at 0 min (adsorption 30 min), 4 min, 8 min, 12 min, 16 min, and 20 min, filtered with a 0.22 μm filter head, and added to a liquid phase vial pre-added with 20 μL of 0.1 mmol / L sodium thiosulfate solution, and the concentration of acetaminophen in the solution was detected by liquid chromatography.

[0066] Figure 8 The figure is a graph showing the degradation effect of iron-doped carbon quantum dots on acetaminophen under different pH conditions in Example 4 of the present invention. Figure 8 It can be seen that the iron-doped carbon quantum dots (Fe-CDs) of the present invention have a removal rate of acetaminophen greater than 95% under the conditions of pH values ​​of 3, 5, 7, and 9, and the degradation efficiency is almost unaffected as the pH value of the acetaminophen solution continues to increase. It can be seen that within a wide pH range, the iron-doped carbon quantum dots (Fe-CDs) of the present invention can effectively activate potassium permonosulfate to efficiently degrade acetaminophen, and have good application potential in a wide range of natural water bodies and various wastewater treatments.

[0067] Embodiment 5:

[0068] The main active species in the photocatalytic degradation reaction process in the method of the present invention are investigated, specifically using iron-doped carbon quantum activated persulfate to degrade acetaminophen-containing water, including the following steps:

[0069] Weigh 9 portions of 1.2 μg of iron-doped carbon quantum dots (Fe-CDs) in Example 1, add them to 50 mL of 2.5 mg / L acetaminophen solution (the initial pH of the solution is 5.8), keep the temperature at 25 ° C using a low-temperature circulating water device, stir in the dark for 30 min to reach adsorption-desorption equilibrium; then, take 8 portions and add anhydrous methanol (MeOH), isopropanol (IPA), sodium azide (NaN3), EDTA-2Na, ammonium oxalate (AO), potassium dichromate, etc. (K2Cr2O7), p-benzoquinone (p-BQ), and methyl sulfoxide (DMSO) were used as quenchers, so that the concentrations of the quenchers in the system were 300mM, 200mM, 20mM, 10mM, 10mM, 10mM, 10mM, 10mM, and 10mM, respectively. After stirring for 2 minutes to mix evenly, potassium permonosulfate (PMS) was added respectively, so that the concentration of PMS in the system was 0.1mM. The photocatalytic degradation reaction was carried out under visible light for 20 minutes to complete the degradation of acetaminophen in the water. In this embodiment, anhydrous methanol is OH and SO4 - · is the quencher, isopropanol is the quencher of ·OH, sodium azide is 1 The quencher of O2, EDTA-2Na is + quencher, AO is h + The quencher is potassium dichromate. - The quencher is O2 for benzoquinone - · Quencher of, methyl sulfoxide is the quencher of Fe(IV).

[0070] During the photocatalytic degradation reaction, 1 mL of the reaction solution was taken at 0 min (adsorption 30 min), 4 min, 8 min, 12 min, 16 min, and 20 min, filtered with a 0.22 μm filter head, and added to a liquid phase vial pre-added with 20 μL of 0.1 mmol / L sodium thiosulfate solution, and the concentration of acetaminophen in the solution was detected by liquid chromatography.

[0071] Fig. 9 The figure is a graph showing the degradation effect of iron-doped carbon quantum dots on acetaminophen under different quenching conditions in Example 6 of the present invention. Fig. 9 It can be seen that the photogenerated holes (h + ) had the strongest inhibitory effect, followed by hydroxyl radicals (·OH) and singlet oxygen ( 1O2), which shows that the degradation process of acetaminophen by photocatalytic activation of potassium permonosulfate by iron-doped carbon quantum dots is a degradation process dominated by photogenerated holes, inducing the generation of other active species, and constructing a high-efficiency oxidation system mixed with a free radical pathway dominated by hydroxyl radicals and a non-free radical pathway dominated by singlet oxygen. This mixed oxidation system not only takes into account the advantages of strong oxidation ability of the free radical pathway, but also takes into account the advantages of a wide oxidation range of the non-free radical pathway, and has good application prospects in actual wastewater treatment.

[0072] In summary, the method of utilizing iron-doped carbon quantum dots to activate persulfate to degrade acetaminophen in water has the advantages of simple process, convenient operation, high treatment efficiency, small amount of oxidant added, good reusability, and environmental friendliness. It can achieve efficient removal of acetaminophen in water, has high use value, and good application prospects.

[0073] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for degrading acetaminophen in water by activating persulfate using iron-doped carbon quantum dots, characterized in that: The method utilizes iron-doped carbon quantum dots to activate persulfate to degrade water containing acetaminophen; the iron-doped carbon quantum dots are prepared by using ferrous gluconate as a raw material through hydrothermal reaction and dialysis; the temperature of the hydrothermal reaction is 180°C to 220°C.

2. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to claim 1, characterized in that: The hydrothermal reaction time is 5 h to 8 h.

3. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to claim 2, characterized in that: The method for preparing the iron-doped carbon quantum dots comprises the following steps: subjecting a ferrous gluconate solution to a hydrothermal reaction, filtering and dialyzing to obtain the iron-doped carbon quantum dots.

4. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to claim 3, characterized in that: The concentration of ferrous gluconate in the ferrous gluconate solution is 0.1 mol / L to 0.3 mol / L, and the preparation process of the ferrous gluconate solution is: mixing ferrous gluconate and water to obtain the ferrous gluconate solution; the mixing time is 10 min to 30 min, and the mixing is performed under stirring conditions.

5. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to claim 4, characterized in that: The pore size of the filter membrane used in the filtration is 0.22 μm, the dialysis time is 24 h to 60 h, the molecular weight of the dialysis bag used in the dialysis is 500 Da, and the dialysis is performed under light-proof conditions.

6. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to any one of claims 1 to 5, characterized in that: The degradation treatment comprises: mixing iron-doped carbon quantum dots with water containing acetaminophen, adding persulfate under light conditions to carry out a photocatalytic degradation reaction, and realizing the degradation of acetaminophen in the water.

7. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to claim 6, characterized in that: The ratio of the iron-doped carbon quantum dots to the water containing acetaminophen is 1 μg-100 μg:1L, and the ratio of the persulfate to the water containing acetaminophen is 50 μmol-500 μmol:1L.

8. The method for degrading acetaminophen in water by activating persulfate with iron-doped carbon quantum dots according to claim 7, characterized in that: The initial concentration of acetaminophen in the acetaminophen-containing water body is 1 mg / L to 20 mg / L, the initial pH value of the acetaminophen-containing water body is 3 to 10, the persulfate is peroxymonosulfate, and the peroxymonosulfate is potassium hydrogen peroxymonosulfate.

9. The method for degrading acetaminophen in water by activating persulfate using iron-doped carbon quantum dots according to claim 8, characterized in that: The mixing time is 30 min to 60 min, the mixing is carried out under light-proof and stirring conditions, the photocatalytic degradation reaction time is 10 min to 20 min, and the photocatalytic degradation reaction temperature is 10° C. to 30° C.

10. The method for degrading acetaminophen in water by activating persulfate using iron-doped carbon quantum dots according to claim 9, characterized in that: The illumination is visible light, the wavelength of the visible light is 420nm, the average light intensity of the visible light is 0.25W-0.35W, and the height of the light source used by the visible light from the water surface is 10cm-20cm.

Citation Information

Patent Citations

  • Method for activating persulfate and removing pollutants and application

    CN109095591A

  • Method for degrading antibiotics by activating persulfate through photoelectric synergistic reinforced iron-based catalyst

    CN114044554A

Cited By

  • Method for removing acetaminophen in water based on visible light excited humic acid activated PMS

    CN119898845A